FUNGSI ATEJI DALAM LIRIK LAGU PADA ALBUM MARGINAL #4 THE BEST ã€ŒSTAR CLUSTER 2ã€ PRODUKSI REJET - M.R., Meisha Putri; Cahyono, Agus Budi (Universitas Negeri Surabaya, 2019)
This article aimed to describe why furigana in Japanese songs often found different furigana actually with kanji below it. Data uses the album MARGINAL # 4 THE BEST ?STAR CLUSTER 2? REJET Production. This study uses qualitative descriptive to examine the type of ateji based on Lewis's theory (2010) and its function based on the theory of Jakobson (1960). Based on analysis, writer find more contrastive ateji than denotive ateji. Fatigue function is found more than other functions. The metalingual function is found on all data.